Cost-Effectiveness of Apatinib and Cabozantinib for the Treatment of Radioiodine-Refractory Differentiated Thyroid Cancer - Shi, Bo; Ma, Wenbiao; Pan, Hongshuai; Shi, Yang; Zhang, Huan; Xing, Shenghai (Frontiers in Pharmacology, 2022)
Background: The effectiveness of apatinib and cabozantinib for the treatment of radioactive iodine–refractory differentiated thyroid cancer (RAIR-DTC) has been demonstrated recently. We aimed to evaluate the cost-effectiveness of these treatments from the Chinese healthcare system perspective. Methods: Two partitioned survival models over a 10-year horizon were built to compare the cost and effectiveness of apatinib vs. placebo and cabozantinib vs. placebo based on the clinical data from the phase 3 randomized REALITY and COSMIC-311 trials. Costs and utility data were obtained from the literature and institutional database. The incremental cost-effectiveness ratio (ICER) was calculated. One-way and probabilistic sensitivity analysis was performed to test the robustness of the conclusion. Results: Apatinib yielded an additional quality-adjusted life-year (QALY) of 0.74 at an additional cost of Chinese Renminbi ¥44,077. The ICER was ¥93,460 (US dollar 13545)/QALY and it was below the current willingness-to-pay (WTP) threshold of ¥217341/QALY. Cabozantinib was associated with an additional QALY of 0.79 at an extra cost of ¥3,55,614 when compared with placebo, and the ICER was ¥4,52,325 (65,554)/QALY, which was above the WTP threshold. The conclusion were robust under one-way and probabilistic sensitivity analysis. The price of cabozantinib has to drop to ¥5.87/mg (39% of the current price) for it has a 50% likelihood of being cost-effective. Conclusion: Apatinib is cost-effective for RAIR-DTC when compared with placebo from the perspective of Chinese healthcare system. However, based on the current evidence, cabozantinib might not be cost-effective and a reduction of price is warranted.